Exploring the DEI mechanisms linking inclusive leadership and hybrid team effectiveness - Wang, Xiaoyan; Hasan, Norhafizah Abu; Ayob, Abu Hanifah (Edelweiss Applied Science and Technology, 2026)
With the development of the new type of work arrangement, the way people work together has changed. As hybrid and remote work arrangements become more common, managing geographically dispersed teams will become more complex. Inclusive leadership has attracted increasing scholarly attention as a potential solution to these challenges. Limited research has examined how diversity, equity, and inclusion (DEI) affect the effectiveness of hybrid teams led by inclusive leaders. This conceptual paper adopts a literature-review approach to synthesize prior studies on inclusive leadership, DEI, and hybrid work. Based on the findings, inclusive leadership can improve the efficiency of hybrid teams by promoting diversity, fostering a sense of fairness among team members, and cultivating a strong sense of belonging. These conditions will promote cooperation among team members and contribute to better outcomes. This paper expands the study of leadership in a hybrid work model by proposing the idea of team DEI. The proposed framework can also help organizations establish high-performing work environments.